PROPOSED STRATEGY IN CHOOSING VALUABLE COMPANIES TO INVEST IN INDONESIA STOCK MARKET BASED ON VALUE INVESTING ANALYSIS - Hadyan Sulistijo, Apta
The stock market sometimes does not reflect the real business, when many businesses suffered by the lockdown regulation and demand shock, the IDX Composite’ level is still increasing even though the real business behind it is the opposite of it. In order to have a safe investment in the stock market it is wise to back to fundamental philosophy behind it which when buy a stock it means buy business behind it not the piece of paper. Therefore, to understand the business behind it, the best method is by analyzing the business’s performance during the pandemic and using several ratios to value the company if it is overvalued or undervalued or so called as value investing. In this thesis, ratio analysis is used to determine the performance and economy condition of the company. Those ratios are inventory turnover ratio, debt-to-equity ratio, profitability ratios, market ratios and also the price analysis. Beside ratio analysis, price analysis is used to determine the intrinsic value of the stock company. The price analysis used in this study are relative value to government bonds, stock as an equity, and annual EPS for projecting an annual compounding return. This price analysis method will give future value of a stock with using its financial performance. The financial performance in this thesis is using two different times. Historical annual report and current annual report. In historical annual in this thesis using for the last 5 years (2015 until 2019). While, for the current financial performance analysis is using the latest 3rd quarter of 2020. After analysis the financial performance and have the intrinsic value result, next is determine the entry point using margin of safety. The margin of safety in this thesis is using 50% margin from stock’s intrinsic value. The intrinsic value is calculated using the earning per share for projecting the next 10 years with discounted factor using 5% inflation per year. Total there are 724 companies which are listed in the Indonesia Stock Exchange. Those 724 companies are categorized into 11 sectors each sectors have its sub-industry. This classification is based on the IDXIC